Pathophysiological effects of SARS-CoV-2 infection on the cardiovascular system and its clinical manifestations—a mini review - Juan Carlos Yugar-Toledo; Louise Buonalumi Tacito Yugar; Luis Gustavo Sedenho-Prado; Roberto Schreiber; Heitor Moreno (Frontiers in Cardiovascular Medicine, 2023)
Coronavirus disease 2019 (COVID-19) is a viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 may have a mild presentation, with few symptoms, or progress to a severe condition, characterized by generalized inflammation, systemic microvascular involvement, coagulopathy, and pulmonary and cardiovascular complications. Men present with more severe symptoms than women, especially men who are older and who present with comorbidities such as hypertension, diabetes mellitus, and a history of atherosclerotic diseases. Owing to its association with endothelial dysfunction, inflammation, thrombosis, and microvascular obstruction, SARS-CoV-2 infection can cause lesions in several organs, including the myocardium and the coronary arterial bed, which can result in clinical manifestations involving the cardiovascular system. In this mini review, we summarize the effects of SARS-CoV-2 infection on the cardiovascular system in both children and adults and characterize the various clinical manifestations associated with this disease.